Analisis Bahan Bakar RON 92 Berbagai Jenis terhadap Performa Kendaraan 150CC - Maulana Malik Fajar N; Mochamad Muzak (Pusat Riset dan Inovasi Nasional, 2024)
The type of fuel is important in a vehicle. At this time there are various types with different brands with different qualities. The objective of the study is to determine the difference of quality with various types of RON 92 fuel on engine performance on a 150 CC combustion motor. The method used in this research is an experimental testing to evaluate the effect of a new treatment with one or more other groups as a comparison. The results showed that statistically using anova on power and torque testing using 3 types of fuel with RON 92 did not get a significant difference. Then the results of fuel consumption testing show different results where the fuel with brand B gets 70.3 ml / 5 minutes with 5000 rpm. The results of statistical exhaust emissions testing also get a difference with the best fuel obtained by using fuel B with the results of CO by 0.43% and HC by 69 ppm.